Pengaruh Latihan Fisik terhadap Kadar Marker Inflamasi pada Pasien Hipertensi Pulmonal - Aziz, Indra Jabbar; Martini, Heny (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Pulmonary hypertension (PH) is characterized by pulmonary vascular dysfunction, which can lead to right heart failure and death, as well as the accumulation of inflammatory cells in the perivascular area. Chronic inflammation plays an important role in the pathophysiology of pulmonary hypertension. Inflammatory markers such as C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) are often elevated in patients with pulmonary hypertension. The accumulation of inflammatory cells accelerates the remodeling process of pulmonary blood vessels and pulmonary hypertension. Despite the current therapeutic approaches for pulmonary hypertension (PH), which aim to improve functional capacity and hemodynamics, pulmonary hypertension remains incurable but remains controllable. Inflammatory processes play a critical role in progressive pulmonary hypertension. Physical exercise can reduce the risk of chronic disease, and recent research has shown that it improves inflammatory marker profiles. This literature review aims to combine evidence on the influence of physical exercise on levels of inflammatory markers in patients with pulmonary hypertension.